2020
DOI: 10.1088/1755-1315/520/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Design of Phycocyanin Production from Spirulina platensis Using Anaerobically Digested Dairy Manure Wastewater

Abstract: Phycocyanin is a blue pigment that is found in cyanobacteria such as Spirulina platensis. Its ability to provide stable and non-toxic blue color makes its market value is so high that it reaches USD 112.3 million in 2018. However, the cultivation of S. platensis to produce phycocyanin can only be carried out by large-scale industry, due to high operating costs of synthetic medium such as Zarrouk. We considered the use of Anaerobically Digested Dairy Manure Wastewater (ADDMW) as an alternative for growth medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The biomass production of S. maxima in different dilutions of ADDMW in Zarrouk medium has not been significantly different, 1.933 ± 0.06 g L -1 and 2.090 ± 0.11 g L -1 , respectively. The same result was found in Taufikurahman et al [8], which grew S. platensis in ADDMW and is different from the control medium in their final dried biomass. As Mulbry and Wilkie [6] mentioned, ADDMW is the liquid waste of manure biodigester and still contains nitrogen and phosphor compounds needed for Spirulina cultivation.…”
Section: S Maxima Growth In Addmwsupporting
confidence: 87%
See 1 more Smart Citation
“…The biomass production of S. maxima in different dilutions of ADDMW in Zarrouk medium has not been significantly different, 1.933 ± 0.06 g L -1 and 2.090 ± 0.11 g L -1 , respectively. The same result was found in Taufikurahman et al [8], which grew S. platensis in ADDMW and is different from the control medium in their final dried biomass. As Mulbry and Wilkie [6] mentioned, ADDMW is the liquid waste of manure biodigester and still contains nitrogen and phosphor compounds needed for Spirulina cultivation.…”
Section: S Maxima Growth In Addmwsupporting
confidence: 87%
“…However, inorganic carbon is still needed to gain optimum growth of Spirulina [4]. A previous study by Taufikurahman et al [8] revealed that ADDMW medium combined with 16.8 g L -1 NaHCO3 and 25 g L -1 NaCl gave the highest phycocyanin productivity from S. platensis. In this study, we combined the utilization of Zarrouk medium with wastewater for other Spirulina species, namely S. maxima, which has never been studied before.…”
Section: Introductionmentioning
confidence: 99%
“…They are either stored as reserve materials or transformed into cell wall components (polysaccharides, etc.). Thus, Taufikurahman, Ilhamsyah, Rosanti, and Ardiansyah (2020) reports that carbohydrate accumulation is inversely proportional to protein concentration.…”
Section: Effect Of Oil Palm Empty Fruit Bunch Medium On the Protein A...mentioning
confidence: 99%
“…Besides the food sector, biomass from A. platensis is also commercially valued as a dietary supplement [1,2,5] since an intake of dried A. platensis has been proven to reduce blood cholesterol levels and improve patients' lipid profiles [6,7]. Recent studies have further attributed anti-inflammatory, immunostimulatory, antioxidant, cancer-inhibiting [8,9] and antiviral [10] properties to cyanobacterial biomass and metabolites [11,12] such as phycocyanin (8-13% w/w of dry biomass [13]) and carotenoids (0.15-0.2% w/w of dry biomass [14]). As an example, Zeaxanthin is believed to reduce the risk of age-related macular degeneration [15,16].…”
Section: Introductionmentioning
confidence: 99%